Answer:
x = -4 2/13
x = -4.15384615385
x = -54/13
(they are all the same, just in different formats)
Step-by-step explanation:
(5/3x) + 6 = (2/9)x
first, make all "x"s have a common denominator
(5/3) = (15/9)
so
(5/3)x = (15/9)x
(15/9)x + 6 = (2/9)x
solve using inverse operations
(15/9)x + 6 = (2/9)x
-(2/9)x -(2/9)x
(13/9)x + 6 = 0
-6 -6
(13/9)x = -6
to get rid of the fraction, multiply the entire equation by the denominator
(13/9)x = -6
*9 *9
13x = -54
/13 /13
x = -4 2/13
x = -4.15384615385
x = -54/13
(they are all the same, just in different formats)